Determination of digestibility and digestible energy of dry velvet (Mucuna pruriens) forage in guinea pigs - Sotelo M., Alejandrina (2020)
This study aimed to determine the apparent digestibility coefficients and digestible energy of dry velvet bean fodder (Mucuna pruriens). The indirect method was used, considering as a basal diet the concentrate used in the university guinea pig farm (Lima, Peru). The experiment had an adaptation phase (14 days) and a faecal collection phase (5 days). Ten adult male 3-month old guinea pigs randomly distributed in individual metabolic cages were used. Five animals were fed the basal diet and the other five with the experimental diet: 80% basal diet and 20% dry velvet bean fodder. The apparent digestibility coefficients obtained for the dry velvet bean were: 66.29% dry matter, 66.13% organic matter, 74.02% crude protein, 50.82% crude fibre, 60.18% ether extract, 78.22% nitrogen-free extract and 73.33% ash. The estimated digestible energy value was 2.61 kcal/g.